Embracing risk in urban education : curiosity, creativity, and courage in the era of "no excuses" and relay race reform - Ginsberg, Alice E. (Rowman & Littlefield Education, 2012)
"Ginsberg argues that in the effort to reduce the achievement gap and mitigate the pejorative label of "at-risk," we are in danger of eliminating risk from education entirely. This is especially the case in urban schools with large numbers of poor and minority students. Ginsberg explores alternative approaches to student achievement at four dynamic Philadelphia public schools"--Provided by publisher